How to Use e-Learning Activities to Connect with the Introvert Corporate Language Learner - Zimmermann, Lisa Birgit (International Journal of Advanced Corporate Learning (iJAC), 2014)
The aim of this contribution is to show some best-practice examples about how to use e-learning activities to connect with introvert learners who must improve their foreign language skills for their jobs. After a short introduction, different possibilities to help the introvert employee to succeed at improving their foreign language skills using an online-learning platform will be presented.